1989
DOI: 10.1104/pp.90.2.398
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Indoleacetic Acid Conjugates in Bean Seeds by Direct Tissue Hydrolysis

Abstract: Gas chromatography-selected ion monitoring-mass spectral analysis using [13Cs]indole-3-acetic acid (IAA) as an internal standard provides an effective means for quantitation of IAA liberated during direct strong basic hydrolysis of bean (Phaseolus vulgaris L.) seed powder, provided that extra precautions are undertaken to exclude oxygen from the reaction vial. Direct seed powder hydrolysis revealed that the major portion of amide IAA conjugates in bean seeds are not extractable by aqueous acetone, the solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…In most studies done over the last 50 years, the amount of auxin obtained after solvent extraction did not account for the total IAA found following exhaustive extraction over time (31,32). More recent studies showed a similar phenomenon, that the amount of total IAA (free plus conjugated) obtained by direct hydrolysis of the tissue was much greater than the amount readily extractable with solvents (12,33,34). This difficulty in accounting for the IAA present in plants has only recently been resolved by the isolation of proteins and peptides to which IAA was attached.…”
Section: Plants Contain Phytohormones In Conjugated Formsmentioning
confidence: 64%
See 3 more Smart Citations
“…In most studies done over the last 50 years, the amount of auxin obtained after solvent extraction did not account for the total IAA found following exhaustive extraction over time (31,32). More recent studies showed a similar phenomenon, that the amount of total IAA (free plus conjugated) obtained by direct hydrolysis of the tissue was much greater than the amount readily extractable with solvents (12,33,34). This difficulty in accounting for the IAA present in plants has only recently been resolved by the isolation of proteins and peptides to which IAA was attached.…”
Section: Plants Contain Phytohormones In Conjugated Formsmentioning
confidence: 64%
“…10 and 11). The amount of IAA released by alkaline hydrolysis of the protein was calculated by the isotope dilution equation (10,12). Molecular Mass Determination of IAP1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bean seeds used in our studies contain large amounts of IAA conjugates, especially amide-linked conjugates: about 600 ng . g-1 fresh weight or 150 ng/seed at full seed maturity (8,9). Their levels decline in the first days of germination but remain relatively high through the later period of germination (11).…”
Section: Discussionmentioning
confidence: 99%